Managing currency crises in emerging markets - Dooley, Michael P. (Michael Patrick), 1944-; Frankel, Jeffrey A. (National Bureau of Economic Research conference report., 2003)
The management of financial crises in emerging markets is a vital and high-stakes challenge in an increasingly global economy. For this reason, it is also a highly contentious issue in today's public policy circles. In this book, leading economists - many of whom have also participated in policy debates on these issues - consider how best to reduce the frequency and cost of such crises. The contributions here explore the management process from the beginning of a crisis to the long-term effects of the techniques used to minimize it.